Pengaruh Profitabilitas, Solvabilitas dan Likuiditas Terhadap Penerimaan Opini Audit Going Concern - Fakhron Hamzah Al-azhar; Nurul Fachriyani (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to determine and obtain empirical evidence of the effect of profitability, solvency and liquidity on the acceptance of going concern audit opinions in infrastructure sector companies listed on the IDX in 2022 to 2024. This study is a quantitative study with secondary data taken from the company's financial statements. The samples in this study used 171 samples collected using the purposive sampling method. The data analysis method in this study used the logistic regression to test the effect of predetermined variables. The results of this study indicate that profitability has a significant negative effect on the acceptance of going concern audit opinions with a significance value of 0.001 and a regression coefficient of -9.912, solvency has a significant positive effect on the acceptance of going concern audit opinions with a significance value of 0.017 and a regression coefficient of 1.109, while liquidity does not have a significant effect on the acceptance of going concern audit opinions with a significance value of 0.942 and a regression coefficient of 0.034. The conclusion of this study is that the auditor uses profitability and solvency as its main consideration on giving the going concern audit opinion, while liquidity is not the main consideration on giving the going concern audit opinion